Uricase immobilized onto nylon tube for use in automated analysis of serum urate - Salleh, Abu Bakar; Ledingham, William M. (Elsevier, 1981)
Uricase is immobilized onto glutaraldehyde-activated nylon tube. Immobilized uricase tube is incorporated into a continuous flow automated analyzer for assaying blood urate. The immobilized enzyme shows good storage and operational stability and the assay system compares favorably with an established method.